Temporospatial study of hexose transporters and mucin in the epithelial cells of chicken (Gallus gallus domesticus) small intestine - Hussar, P; Kaerner, M; Duritis, I; Plivca, A; Pendovski, L; Jaerveots, T; Popovska-Percinic, F (My University, 2017)
The temporospatial patterns in the localization of hexose transporters as well as in the quantitative and qualitative differences of glycoprotein mucin produced by the goblet cells of broiler chicken (Gallus gallus domesticus) small intestine during their first postnatal month were studied. The integral membrane proteins glucose transporter-2 and -5 (GLUT-2 and GLUT-5) that facilitate the transport of hexoses across epithelial cell layers that separate distinct compartments in organism were detected in the chicken intestinal epithelial cells using immunohistochemical labeling with polyclonal primary antibodies Rabbit anti-GLUT-2 and Rabbit anti-GLUT-5 (IHC kit, Abcam, UK). The chemical composition of mucin (neutral, acid) was carried out by applying the histochemical reactions by Alcian-Blue and periodic acid-Schiff methods. The results revealed presence of the hexose transporters GLUT-2 and -5, immunolocalized in the enterocytes of broiler's small intestine and the temporospatial pattern of the density of goblet cells of intestinal mucosa as well as the chemical composition of mucin produced by the goblet cells in chicken immediately after hatching and in 30-days-old chicken's. Simultanously, when goblet cells remained unstained with both antibodies in intestinal epithelium in chicken of both ages or some moderate staining was noticed in 30-days-old chickens' ileal epithelium, the increase of neutral and acid mucin- containing cells per area unit in both segments of the small intestine was detected from the first day after hatching to 30 day of life and the densilty of goblet cells was found to be higher in ileal than in duodenal region.